NEMIPTERUS DELAGOAE SMITH (NEMIPTERIDAE: PISCES) A NEW RECORD FROM THE INDIAN SEAS - Rajagopalan, M; Karuppaswamy, P; Regunathan, A (Indian Journal of Fisheries, 2011)
The occurrence of Nemipterus delagoae Smith is reported here for the first tiiiÂ» from the Indian seas based on one specimen 231 mm total length, collected from 40-m depth at 9Â°35’N 76Â°05’E along the southwest coast of India, The species is described and illustrated